Innovation job performance in industrial context: the role of perceived of organizational support for creativity and climate of innovation toward employee learning orientation - Rosyidi, Luthfi Nur; Mudzakkir, Mohammad Fakhruddin; Choirunnisa, Zuyyinna; Nur Lailiyah, Ilfiah; Indrio, Ludita Woro (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
This study has a purpose to examine the factors that influence employee innovation performance such as climate of innovation, employee learning orientation, and organizational support for creativity. The object of research is one of the manufacturing companies, State-Owned Enterprises, especially in departments that are required to have high innovation such as marketing, Human Resources, and others. A quantitative approach with PLS 3.0 was used to analyze the data collected through distributing questionnaires on a Likert scale with 229 valid questionnaires collected. The results showed that all variables used had a positive influence. Innovation climate and organizational support for creativity affect learning orientation because a good innovation climate and organizational support for creativity will encourage organizational efforts to optimize learning for employees. While the climate of innovation, organizational support for creativity, and learning orientation affect innovation performance because the climate of organizational innovation and organizational support through training and learning can affect the way employees work and encourage employees to improve innovation performance. Future research is expected to conduct further analysis by comparing between different companies.